NCAA March Madness - Coyte G. Cooper; Andrea Eagleman; Pamela C. Laucella (University of Kansas Libraries, 2009)
In today's economic environment, the United States newspaper industry has realized a severe period of decline in terms of circulation and overall consumer interest (Sullivan-Getty, 2009). While several major newspapers ceased existence in 2008, the USA Today remained the most popular American newspaper with a daily circulation well over 2.2 million (Sutel, 2008). However, with recent changes in consumer travel, the newspaper is expected to lose its position as the top U.S. daily following a 17% drop in circulation from April to September (Vanacore, 2009). With this in mind, it is critical that the USA Today identifies business strategies that will allow it to increase its circulation in years to come. In particular, it is more important than ever that the newspaper is aware of the content being delivered to consumers to ensure that it is delivering a highly competitive product. Thus, the purpose of the study is to investigate the coverage during the men's and women's NCAA Basketball Championships to determine whether the newspaper is providing content to maximize its potential reach with sport consumers.